Are sustainable health workforces possible?: issues and a possible remedy - Rees, Gareth H. (2023)
The 2020–2022 period of the global COVID-19 pandemic exposed the fact that many countries health systems had inadequate health workforce availability. This is despite sustainable health workforces being critical to health service and healthcare delivery, an acknowledgement that drove the significant investment and focus on health workforce development over the previous two decades. As such, this review article discusses health workforce governance and planning, notes its weaknesses, and identifies some of the barriers to the implementation of health workforce policy making and planning and the achievement of sustainable health workforces. Important is the recognition that health workforce planning is long-term in nature, while health workforce decision-making processes are dominated by political processes that have much shorter time frames. The article concludes by offering the approach of backcasting to overcome this dichotomy.